ՀՀ սննդարդյունաբերության ոլորտում շրջանաձև բիզնես մոդելների մշակման անհրաժեշտությունը և դրանց ներդրման հեռանկարները - Ալեքսանյան, Վարդան; Մարկոսյան, Դավիթ (ՀԱԱՀ հիմնադրամ)
В последние годы неэффективное управление ресурсами в пищевой промышленности привело к ряду экологических проблем, требующих системных решений. Следовательно, необходимо разработать и внедрить циркулярные бизнес-модели, которые позволят сократить растрачивание ресурсов и будут способствовать устойчивому экономическому развитию. Изучена связь между производством продуктов питания и рядом социально-экономических и экологических факторов. Проведен корреляционно-регрессионный анализ, а также предоставлены рекомендации бизнес-сообществу и политикам в этой области, основанные на используемых в международной практике циркулярных бизнес-моделях. Inefficient resource management in the food industry has led to significant environmental challenges, necessitating systemic solutions. This study analyzes the relationship between food production and various environmental impact indicators, revealing a strong positive correlation between food production and greenhouse gas emissions, highlighting the industry’s contribution to climate change and other environmental risks. As a result of the study, moderate to strong correlations were observed between food production, hazardous waste generation, and wastewater volumes, indicating inefficiencies in production processes and waste management. The findings also suggest a negative impact of unsustainable practices on overall quality of life, as an indicator of the social dimension within sustainable development. To address these issues, implementing circular business models is crucial. These models emphasize waste minimization, resource efficiency, and sustainable economic development. Key recommendations include improving harvesting techniques, better storage facilities, valorization of by-products, and fostering collaboration among producers. With transforming the production processes and adopting innovative business strategies, the food industry can balance economic growth with environmental and social responsibility.
Keywords: Ագրոբիզնես